Makna Simbolik Ibadah Haji Perspektif Ali Syariati - Ahmad Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2022)
In this study, the author wants to reveal the secret of the meaning of the rituals of Hajj according to Ali Shariati with a philosophical approach. The results of the study explain that the essence of the Hajj ritual according to Ali Shariati is the existential evolution of humans towards God, which is a symbolic drama of the philosophy of the creation of Adam's children and grandchildren. The symbols in the Hajj ritual include the Miqat is a symbol of liberation from selfishness, Ihram is a symbol of purity and equality, the Kaaba is a symbol of God's decree and immortality, Black Stone is a symbol of the oath of allegiance, Maqam Ibrahim is a symbol of historical reality, Sa' i is a symbol of optimism in life, Arafah is a symbol of knowledge and wisdom, Masy'aril haram (Muzdalifah) is a symbol of awareness and intuition, Mina is a symbol of love and martyrdom, Throwing Jumrah is a symbol of jihad against the trinity of kabilism, Cutting hair (tahallul) is a symbol of human gratitude, and Kurban is a symbol of absolute surrender and the fusion of hayawaniyah nature.